2016
DOI: 10.3390/su8101083
|View full text |Cite
|
Sign up to set email alerts
|

Model of Chinese Household Kitchen Waste Separation Behavior: A Case Study in Beijing City

Abstract: High participation rates by the public in authority projects are key in increasing resident recycling levels. Understanding waste separation behavior is crucial to achieving sustainable waste management within such household-based schemes. To identify the driving forces behind the seldom-discussed kitchen garbage separation behavior, five psychological factors, namely, attitude, perceived behavior control, subjective norms, moral norms, and responsibility denial, are established. Our data originate from a soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 62 publications
6
56
0
Order By: Relevance
“…The direct path from perceived behavioural control to intention/behaviour is assumed to display the influence between actual ease and difficulty with intention/behaviour. In this study, a significant path from perceived Attitude that stresses moral obligation towards the environment draws attention to personal beliefs on rights and responsibilities [35]. Hence, an individual who has a high perception of moral obligations often manages their thoughts and follow the discipline, which may enhance a stronger attitude towards being environmental-friendly.…”
Section: Hypothesis 3 (H3) Subjective Norm Has Positive Influence Onmentioning
confidence: 99%
See 3 more Smart Citations
“…The direct path from perceived behavioural control to intention/behaviour is assumed to display the influence between actual ease and difficulty with intention/behaviour. In this study, a significant path from perceived Attitude that stresses moral obligation towards the environment draws attention to personal beliefs on rights and responsibilities [35]. Hence, an individual who has a high perception of moral obligations often manages their thoughts and follow the discipline, which may enhance a stronger attitude towards being environmental-friendly.…”
Section: Hypothesis 3 (H3) Subjective Norm Has Positive Influence Onmentioning
confidence: 99%
“…Barr and Gilg discussed that past behaviour is a self-reinforcing process which provides an important reference for subsequent behaviour [35], hence an individual who conforms to a particular behaviour will be more inclined to perform it again. Furthermore, according to TPB, perceived behavioural control is one of the direct constructs in predicting intention and behaviour.…”
Section: Other Possible Influential Factors On Pro-environmental Intementioning
confidence: 99%
See 2 more Smart Citations
“…Beyond these basic factors, several studies and surveys have found that consumers' culinary skills and, more generally, information and awareness on the wider implications of food (e.g., nutritional properties and related dietary effects, conditions of safe use, cultural aspects, social and environmental implications) have a positive correlation with a reduced generation of FW in the households, since they contribute to create a positive attitude towards good practices at different levels: planning of food shopping and meals at home, food storage, meal preparation and portioning, reuse of leftovers and optimisation of food available at home, donation of the food that cannot be consumed for any reason, and sorting of kitchen waste [13][14][15]17,22,25,104,134,147,153,154,158,[175][176][177].…”
Section: Fw Drivers Related To Consumers' Individual Behaviours Modifmentioning
confidence: 99%